PYROLYSIS OF WASTE WOOD (Innovation in Woodworking Industry and Engineering design, 2026)
The fast and slow pyrolysis is a both flexible and an attractive method for converting bio-mass into easy to store and transport products that are used both as an energy source and a feedstock for chemical production. Considerable efforts have been made to convert wood bio-mass to liquid fuels, energy and chemicals since the oil crisis in the middle of 1970. The aim of the current review is to summarize investigations before 2010 year for understanding of process of pyrolysis. In this review are discussed publications for pyrolysis of waste wood from beech, oak, poplar, pine and other species from 2010 to 2014 years.